Adiponectin receptor T-cadherin emerges as a novel regulator of adipose stem cell quiescence and adipogenesis - Sysoeva, V. Yu; Arbatsky, M. S.; Kulebyakin, K. Yu; Tyurin-Kuzmin, P. A.; Semina, E. V.; Klimovich, P. S.; Brodsky, I. B.; Romashin, D. D.; Altyeva, A. F.; Voloshin, N. S.; Kalinina, N. I.; Vigovskiy, M. A.; et al. (Frontiers in Cell and Developmental Biology, 2026)
The question of heterogeneity among adipose tissue cells and mesenchymal stem/stromal cells mesenchymal stem cells derived from white adipose tissue has long been a subject of interest. In our study, we conducted a comprehensive single-cell RNA-seq analysis on MSCs isolated from human subcutaneous adipose tissue and maintained under control conditions or upon adipogenic induction. Our findings unveiled a distinct subpopulation of T-cadherin expressing cells, which co-expressed Dipeptidyl peptidase–4 (DPP4+), a marker of multipotent progenitors in the adipose tissue. Moreover, T-cadherin co-expressed with DPP4+ in early progenitors both, in vivo and in vitro. While adipogenic induction resulted in overall T-cadherin decline, in both the control and differentiated samples, there existed cells with high T-cadherin concurrently expressing stemness-related genes. Pseudotemporal trajectories analysis based on the scRNA-seq data, revealed that T-cadherin-expressing cells constituted a discrete cell subpopulation with stem-like properties, rather than participating in adipogenic differentiation. Using lentiviral transduction, we manipulated T-cadherin expression in MSCs and found that cells overexpressing T-cadherin also displayed an elevated level of DPP4. Strikingly, these cells exhibited significantly slower rates of proliferation compared to the controls. Long-term live-cell imaging, which allowed for the tracking of individual cell fates over a span of 10 days, together with classical adipogenic differentiation assays, revealed a substantial reduction in adipogenic differentiation capacity among MSCs overexpressing T-cadherin. Consequently, our experimental findings support a compelling model wherein T-cadherin, positioned upstream of DPP4, plays a pivotal role in maintaining a stem-like status within a distinct subpopulation of T-cadherin-expressing cells within MSCs.